Screening the Toxicity and Biodegradability of Petroleum Hydrocarbons by a Rapid Colorimetric Method - Montagnolli, Renato Nallin; Lopes, Paulo Renato Matos; Bidoia, Ederio Dino (Archives of environmental contamination and toxicology, 2015)
Crude oil and petroleum products have a wide variety of hazardous components with high toxicity and low biodegradability. Certain dyes change their colors by intercepting electron transfer reactions during the transformation processes. This study applied resazurin and 2,6-dichlorophenol-indophenol indicators for a rapid screening biodegradation capability and toxicity response to various petroleum products such as motor oil, diesel, gasoline, and phenol. Colorimetry tests were performed in test tubes, and the absorbance values were measured over time. We observed different discoloration profiles after degradation tests using Bacillus subtilis inoculum. Phytotoxicity assays were also performed to compare colorimetric screening assays with a conventional toxicity testing with plants (seed germination). The results indicated that biotransformation of oils can increase its overall toxicity. Intermediate byproducts can be formed through biodegradation and thereby increase the toxicity of oils. The assessment of acute toxicity has shown that phenol is extremely toxic to petroleum-biodegrading microbial communities. Low molecular-weight gasoline was considered biodegradable, but it also exhibited a high acute toxic effect, mainly due to its high solubility and the presence of more volatile compounds that can penetrate cells and potentially damage cellular structures.